Policy discourses on climate change, peace, and security in Somalia - Schapendonk, Frans; Scartozzi, Cesare (2024)
The objective of this brief is to detect and evaluate the in-text presence of particular topics and discursive framings related to the climate, peace, and security nexus in Somalia, thereby revealing trends of successful – or conversely, gaps – in understanding and engagement with the nexus. Secondly, this analysis aims to provide a measure with regards to the degree to which cross-sectoral and cross-scalar integration and coherence is evident between different sectors deemed relevant to managing and preparing for climate-related security risks in Somalia by recording in-text references to other sectors or instances of coordination between sectoral actors. In pursuing these two objectives, this brief provides a snapshot of the current ‘state of play’ of a given policy landscape in terms of how well equipped it is to detect, prepare for, and mitigate complex climate-related security risks.